Pengaruh Religiusitas Terhadap Impulse Buying dengan Intensitas Penggunaan Paylater Sebagai Variabel Intervening pada Generasi Milenial - Faiqul Hazmi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
This study reveals the role of religiosity in influencing of impulsive buying risk. almost of the online shopping provide a paylater feature that helps users to purchase goods with payment at a later date (online debt). The object of this research is the millennial generation. The method used is quantitative using SmartPLS as a statistical tool. The results show that (1) The level of religiosity has a negative effect on impulse buying, meaning that the more religious a person will decreases of impulsive buying behavior; (2) Religiosity has a significant negative effect on the intensity of using paylater, meaning that the more religious a person will decrease behavior of indebtedness through paylater on online shopping; (3) The intensity of using paylaters has a significant positive effect on impulse buying, meaning that debt behavior through paylaters risks increasing impulsive purchases; (4) Religiosity has a significant negative effect on impulse buying with the intensity of using paylater as an intervening variable. This indicates that Religiosity is a variable that negatively affects impulse buying, so that the dimensions in Religiosity can be strengthened, which can reduce wasteful and wasteful lifestyles. caused by impulsive purchases without going through careful purchase considerations.